Cover Image. (14th May 2020) - Yang, Yongliang; Vamvoudakis, Kyriakos G.; Modares, Hamidreza
Abstract : The cover image is based on the Research Article Safe reinforcement learning for dynamical games by Yongliang Yang et al., https://doi.org/10.1002/rnc.4962 . Abstract : The cover image is based on the Research Article Safe reinforcement learning for dynamical games by Yongliang Yang et al., https://doi.org/10.1002/rnc.4962 .